Prevalence of eating disorders in elite athletes is higher than in the general population - Sundgot-Borgen, J.; Torstveit, M. K. (Clinical Journal of Sport Medicine, 2004)
Objective: The objectives of the study were to examine the prevalence of anorexia nervosa (AN), bulimia nervosa (BN), anorexia athletica (AA), and eating disorders not otherwise specified (ED-NOS) in both male and female Norwegian elite athletes and a representative sample from the general Norwegian population. Design: A 2-step study including self-reported questionnaire and clinical interview. Setting/Participants: The entire population of Norwegian male and female elite athletes (n = 1620) and controls (n = 1696) was evaluated for the presence of eating disorders (EDs). Main Outcome Measurement: Based on the results of the questionnaire, all athletes and controls classified as at risk for EDs, and a representative sample of athletes and controls classified as healthy participated in the clinical part of the study to determine the number of subjects meeting the Diagnostic and Statistical Manual of Mental Disorders-IV criteria for EDs. Results: More athletes (13.5%) than controls (4.6%; P < 0.001) had subclinical or clinical EDs. The prevalence of EDs among male athletes was greater in antigravitation sports (22%) than in ball game (5%) and endurance sports (9%; P < 0.05). The prevalence of EDs among female athletes competing in aesthetic sports (42%) was higher than that observed in endurance (24%), technical (17%), and ball game sports (16%). Conclusions: The prevalence of EDs is higher in athletes than in controls, higher in female athletes than in male athletes, and more common among those competing in leanness-dependent and weight-dependent sports than in other sports. A collaborative effort among coaches, athletic trainers, parents, physicians, and athletes is optimal for recognizing, preventing, and treating EDs in athletes. In general, studies have suggested a higher frequency of eating problems in athletes than in nonathletes, particularly in athletes competing in sports that emphasize leanness or a low body weight. 1-6 However, some studies suggest a similar or lower risk for eating disorders (EDs) compared with controls for female athletes in aesthetic sports 7 and running 8,9 and female athletes of lower competitive level. 10 Of the few studies that include male athletes, some indicate an increased risk for EDs in male athletes competing in weight class sports such as wrestling and rowing, 11-13 and others indicate a lower risk for EDs in male figure skaters 14 and swimmers. 15 Athletes constitute a unique population, and the impact of factors such as training, eating pattern, extreme diets, restriction of food intake, and psychopathological profile must be evaluated differently from this impact in nonathletes. 16-18 Therefore, the concept of anorexia athletica (AA) 16 has been introduced. AA allows identification of athletes with symptoms of EDs who do not meet all diagnostic criteria for anorexia nervosa (AN) or bulimia nervosa (BN). 16 The athlete with AA demonstrates an intense fear of gaining weight or becoming fat, even though he/she is underweight (at least 5% less than expected normal weight for age and height for the general population). This low body weight is attained by a reduction in energy intake, excessive exercising (more than is required to improve performance), or both. Frequently, the athlete with AA will also report bingeing, self-induced vomiting, and using laxatives or diuretics. 16 The athletes with subclinical EDs, such as eating disorders not otherwise specified (ED-NOS) or AA, may show evidence of some of the common psychologic traits associated with the clinical EDs, such as high achievement orientation, obsessive-compulsive tendencies, and perfectionism. However, these traits are generally expected and usually essential for competing successfully. 19